Global Ionospheric and Thermospheric Effects of the June 2015 Geomagnetic Disturbances: Multi‐Instrumental Observations and Modeling. Issue 11 (20th November 2017) - Astafyeva, E.; Zakharenkova, I.; Huba, J. D.; Doornbos, E.; van den IJssel, J.
Abstract: By using data from multiple instruments, we investigate ionospheric/thermospheric behavior during the period from 21 to 23 June 2015, when three interplanetary shocks (IS) of different intensities arrived at Earth. The first IS was registered at 16:45 UT on 21 June and caused ~50 nT increase in the SYM ‐ H index. The second IS arrived at 5:45 UT on 22 June and induced an enhancement of the auroral/substorm activity that led to rapid increase of thermospheric neutral mass density and ionospheric vertical total electron content at high latitudes. Several hours later, topside electron content and electron density increased at low latitudes on the nightside. The third and much larger IS arrived at 18:30 UT on 22 June and initiated a major geomagnetic storm that lasted for many hours. The storm provoked significant effects in the thermosphere and ionosphere on both dayside and nightside. In the thermosphere, the dayside neutral mass density exceeded the quiet time levels by 300–500%, with stronger effects in the summer hemisphere. In the ionosphere, both positive and negative storm effects were observed on both dayside and nightside. We compared the ionospheric observations with simulations by the coupled Sami3 is Also a Model of the Ionosphere/Rice Convection Model (SAMI3/RCM) model. We find rather good agreement between the data and the model for the first phase of the storm, when the prompt penetration electric field (PPEF) was the principal driver. At the end of the storm main phase, when the ionospheric effects were, most likely, driven by a combination of PPEF and thermospheric winds, the modeling results agree less with the observations. Key Points: We analyze global ionospheric/thermospheric effects of geomagnetic disturbances (substorms and major storm) occurred on 22‐23 June 2015 The storm caused quite significant effects in the ionosphere and thermosphere on both dayside and nightside SAMI3/RCM model shows rather good agreement with observations at the first stage of the storm, but less agreement is found at the end of the storm